2009
DOI: 10.1002/path.2536
|View full text |Cite
|
Sign up to set email alerts
|

Advanced lipoxidation end‐products mediate lipid‐induced glomerular injury: role of receptor‐mediated mechanisms

Abstract: Atherosclerosis and renal disease are related conditions, sharing several risk factors. This includes hyperlipidaemia, which may result in enhanced lipoprotein accumulation and chemical modification, particularly oxidation, with formation of advanced lipoxidation endproducts (ALEs). We investigated whether increased lipid peroxidation plays a major role in the pathogenesis of lipid-induced renal disease, via receptor-mediated mechanisms involving the scavenger and advanced glycation endproduct (AGE) receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 46 publications
(63 reference statements)
6
66
1
1
Order By: Relevance
“…Moreover, both circulating and renal tissue levels of AGEs increased more markedly in response to diabetes and renal cortex RAGE expression was up-regulated even in control animals and increased in a significantly higher extent in diabetic mice. Similar features of more marked fibrosis and inflammation were observed in the aging [78], AGE-injection [79], and HFD [80] models.…”
Section: Galectin-3 As a Disease Mediator: Animal Studiessupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, both circulating and renal tissue levels of AGEs increased more markedly in response to diabetes and renal cortex RAGE expression was up-regulated even in control animals and increased in a significantly higher extent in diabetic mice. Similar features of more marked fibrosis and inflammation were observed in the aging [78], AGE-injection [79], and HFD [80] models.…”
Section: Galectin-3 As a Disease Mediator: Animal Studiessupporting
confidence: 60%
“…In contrast with findings in the kidney and the aorta, where galectin-3 ablation was associated with an exacerbation of the disease [77][78][79][80][81], in the liver of the same animals, HFD-induced non-alcoholic steatohepatitis (NASH) was attenuated by galectin-3 ablation, as indicated by the lower extent of inflammation and fibrosis, the two hallmarks of NASH. Consistently, liver AGE and ALE levels and RAGE expression were decreased in galectin-3 deficient mice as opposed to wild-type.…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 67%
“…Nevertheless, some Authors [26,27] suggested that Gal-3 can influence modified-LDL uptake by macrophages; particularly, Gal-3 has been demonstrated to play a major role in transforming macrophages into foam cells, which secrete Gal-3, attracting monocytes and macrophages. However, Gal-3 might influence plaque progression also avoiding the effective removal of modified lipoproteins, as shown by Iacobini in an experimental study in mice [28]. As suggested by an in vitro study, another observation supporting the pro-atherogenic role of Gal-3 is its binding with Lipopolysaccharide (LPS), which in turn exerts several pro-atherogenic effects [29].…”
Section: Galectin-3 and Atherosclerosismentioning
confidence: 96%
“…125 Increased AGE and RAGE levels, macrophage infiltration, fibrosis, and inflammation are found in the kidneys of mice that develop glomerular disease from an atherogenic high-fat diet; this lipid-induced renal injury is regulated in part by galectin-3. 126 TLR4 is up-regulated in mouse models of cryoglobulinemic membranoproliferative glomerulonephritis and localizes to podocytes of nephritic glomeruli; stimulation of podocytes with either TLR4 ligands or fibrinogen results in similar patterns of enhanced chemokine expression, suggesting that TLR4 functions as a DAMPs receptor for endogenous ligands and may mediate glomerular injury by stimulating innate immunity. 127 In nephrotoxic nephritis, a model of rapidly progressive glomerulonephritis, Hsp60 is released from kidneys and excreted in urine, and administration of Hsp60 exacerbates disease in a T cell-dependent manner.…”
Section: Diabetic Nephropathy and Nondiabetic Glomerular Diseasesmentioning
confidence: 99%